Research progress of Yttrium-90 microsphere selective internal radiation therapy in downstaging and conversion of hepatocellular carcinoma - Licong LIANG; Yuchan LIANG; Wensou HUANG; Yongjian GUO; Jingjun HUANG; Liteng LIN; Mingyue CAI; Kangshun ZHU (Zhongguo Linchuang Yixue)
The incidence and mortality of hepatocellular carcinoma (HCC) in China are among the highest in the world, imposing a heavy social burden. Liver resection and liver transplantation are the primary radical treatments for HCC, although most patients are no longer able to meet the surgical requirements at initial diagnosis. Yttrium-90 microsphere selective internal radiation therapy (90Y-SIRT) has the advantages of shrinking tumors, enlarging residual liver, regressing portal vein tumor thrombus and improving the quality of life, which can be used for conversion, downstaging and bridging therapy for HCC before surgical treatment, enabling patients regain the chance of radical treatment and reducing the postoperative recurrence rate. This review focuses on the clinical application and progress of 90Y-SIRT in this field.